Urbanizing degrowth: Five steps towards a Radical Spatial Degrowth Agenda for planning in the face of climate emergency. (May 2023) - Kaika, Maria; Varvarousis, Angelos; Demaria, Federico; March, Hug
We call for coupling degrowth with urban studies and planning agendas as an academically salient and politically urgent endeavour. Our aim is threefold: to explore ways for 'operationalising' degrowth concepts into urban and regional everyday spatial practices; to sketch pathways for taking degrowth conceptually and methodologically beyond localised experiments and inform larger scale planning practices and international agendas; and to critically assess the multiple ways in which such a radical urban degrowth agenda will have to differ in the Global North and in the Global South. We outline five steps for such a programmatic, yet paradigmatic, urban degrowth agenda. These are: (1) grounding current degrowth debates within their historical–geographical context; (2) engaging (planning) institutions in linking degrowth practices to urbanisation policies; (3) examining how urban insurgent degrowth alliances can be scaled up without co-optation; (4) focusing on the role of experts and professionals in bringing degrowth principles into everyday urban practice; and (5) prefiguring how degrowth agendas can confront the diverse and unequal urban social relations and uneven outcomes in the Global North and South.